Adsorção e lixiviação de trifluralin e imazaquin em diferentes solos - PIRES, NADJA DE MOURA; SILVA, JOSÉ FRANCISCO DA; SILVA, JOÃO BATISTA DA; FERREIRA, LINO ROBERTO; CARDOSO, ANTONIO AMÉRICO (Revista Ceres, 2015)
.